Ca(2+) and Ionic Strength Dependencies of S1-ADP Binding to Actin-Tropomyosin-Troponin: Regulatory Implications - Gafurov, Boris (Biophysical Society, 2004)
Skeletal and cardiac muscle contraction are inhibited by the actin-associated complex of tropomyosin-troponin. Binding of Ca(2+) to troponin or binding of ATP-free myosin to actin reverses this inhibition. Ca(2+) and ATP-free myosin stabilize different tropomyosin-actin structural arrangements. The position of tropomyosin on actin affects the binding of ATP-free myosin to actin but does not greatly affect myosin-ATP binding. Ca(2+) and ATP-free myosin alter both the affinity of ATP-free myosin for actin and the kinetics of that binding. A parallel pathway model of regulation simulated the effects of Ca(2+) and ATP-free myosin binding on both equilibrium binding of myosin-nucleotide complexes to actin and the general features of ATPase activity. That model was recently shown to simulate the kinetics of myosin-S1 binding but the analysis was limited to a single condition because of the limited data available. We have now measured equilibrium binding and binding kinetics of myosin-S1-ADP to actin at a series of ionic strengths and free Ca(2+) concentrations. The parallel pathway model of regulation is consistent with those data. In that model the interaction between adjacent regulatory complexes fully saturated with Ca(2+) was destabilized and the inactive state of actin was stabilized at high ionic strength. These changes explain the previously observed change in binding kinetics with increasing ionic strength.